Leydig cell tumor of ovary with primary hyperparathyroidism: A rare association - Chittamuri, Suhitha; Ayyagari, Mythili; Atla, Bhagyalakshmi; Kandregula, Subrahmanyam A.V. (International Journal of Research in Medical Sciences, 2017)
Leydig cell tumors of ovary are extremely rare sex cord stromal tumors that account for <0.2% of ovarian cancers. Most of these tumors can cause hyperandrogenism. A 54 year old multiparous postmenopausal woman, known diabetic and hypertensive, presented with progressive virilization, bone pains and depressed mood for 2 years. Diagnostic evaluation revealed markedly elevated testosterone with normal dehydroepiandrosterone sulphate. Computerized tomography of abdomen showed right ovarian mass with multiple cysts in both kidneys. Biochemical investigations revealed hyperglycemia, hypercalcemia, hypophosphatemia and elevated parathormone (PTH) levels. Sestamibi scan for parathyroids was suggestive of right inferior parathyroid adenoma. Histopathology of the resected right ovarian tumor was consistent with leydig cell tumor of ovary. Postoperatively serum testosterone and blood glucose levels were normalized, but PTH levels remained high. PTH levels were normalized after resection of parathyroid adenoma